The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/pola.24151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, electrochromic properties, and electrochromic device application of a novel star polymer consisting of thiophene end‐capped poly(ε‐caprolactone) arms emanating from a hexafunctional cyclotriphosphazene core

Abstract: Hexa‐armed and thiophene (Thi) end‐capped poly(ε‐caprolactone) star polymer (N3P3‐(PCL‐Thi)6), containing cyclotriphosphazene core, was prepared in a four‐step reaction sequence. Ring‐opening polymerization (ROP) and “click chemistry” techniques were employed in the first and final steps, respectively. Hexa‐armed PCL star polymer (N3P3‐(PCL‐OH)6) was successfully synthesized via ROP of ε‐caprolactone (ε‐CL) by using hekzakis(p‐(hydroxymethyl)phenoxy) cyclotriphosphazene as the multisite initiator and tin(II) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…30 Liu and coworkers prepared dansyl-labeled poly(N-isopropylacrylamide) microgels to be used as fluorescent Cu 21 sensor and showed that thermo-induced collapse of the sensing material remarkably increased its detection sensitivity. 34 Phosphonitrilic trimer derivatives having proper functional groups have been employed as the connecting (core) unit for the preparation of star-shaped polymers via corefirst (divergent) 35,36 and arm-first (convergent) approaches. 32,33 They have less entanglement in the solid state, high solubility in various organic solvents, as well as lower solution and bulk viscosities compared to linear ones having similar molecular weights.…”
Section: And Zhongmentioning
confidence: 99%
“…30 Liu and coworkers prepared dansyl-labeled poly(N-isopropylacrylamide) microgels to be used as fluorescent Cu 21 sensor and showed that thermo-induced collapse of the sensing material remarkably increased its detection sensitivity. 34 Phosphonitrilic trimer derivatives having proper functional groups have been employed as the connecting (core) unit for the preparation of star-shaped polymers via corefirst (divergent) 35,36 and arm-first (convergent) approaches. 32,33 They have less entanglement in the solid state, high solubility in various organic solvents, as well as lower solution and bulk viscosities compared to linear ones having similar molecular weights.…”
Section: And Zhongmentioning
confidence: 99%
“…In this manner, azide functional units of (S1‐S3)‐N 3 were reacted with alkyne unit of 1‐ethynylpyrene, providing pyrene‐functional styrenic star copolymers [ (S1‐S3)‐Pyr ]. Click reactions have considerably high compatibility to various functional units and solvents and give regiospecific 1,3‐cycloaddition products with near quantitative yields under mild reaction conditions …”
Section: Resultsmentioning
confidence: 99%
“…Star-shaped polymers consist of several linear chains connected to a central core and have many advantages due to their compact molecular shapes, highly branched structures and unique rheological properties [24][25][26][27][28][29][30][31][32][33][34]. They are highly soluble in organic solvents, have smaller hydrodynamic volume and radius of gyration, resulting in their lower solution and melt viscosities with respect to linear polymers with similar molecular weights [32].…”
Section: Introductionmentioning
confidence: 99%